PARADIGMA KH. ALI YAFIE TERHADAP SUMBER- SUMBER HUKUM ISLAM - Anwar Sadat (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2012)
This article reviews the paradigm Yafie KH.Ali thinking about the sources of Islamic law in particular sources of law that has been agreed upon. The method used is a literature review with a direct look at various sources or manuscript is an original work of KH Ali Yafie. Ali Yafie figure was one of the active transform thinking through scholarly writings. Primarily covering the social, political, economic, and health dimensions of Islamic studies (Islamic studies).